Transforming NATO new allies, mission, and capabilities - Ivanov, Ivan Dinev (Lexington Books, 2011)
Transforming NATO: New Allies, Missions, and Capabilities, by Ivan Dinev Ivanov, examines the three dimensions of NATO's transformation since the end of the Cold War: the addition of a dozen new allies; the undertaking of new missions such as peacekeeping, crisis response, and stabilization; and the development of new capabilities to implement these missions. This book explains these processes through two mutually reinforcing frameworks: club goods theory and the concept of complementarities. NATO can be viewed as a diverse, heterogenous club of nations providing collective defense to its members, who, in turn, combine their military resources in a way that enables them to optimize the alliance's capabilities needed for overseas operations. Transforming NATO makes a number of theoretical contributions. First, it offers new insights into understanding how heterogeneous clubs operate. Second, it introduces a novel concept, that of complementarities. Finally, it reevaluates the relevance of club goods theory as a framework for studying contemporary international security. These conceptual foundations apply to areas well beyond NATO. They provide useful insights into understanding the operation of transatlantic relations, alliance politics, and a broader set of international coalitions and partnerships.